Depletion of superjunction power MOSFETs visualized by electron beam induced current and voltage contrast measurements. Issue 11 (8th August 2014) - Kirnstoetter, Stefan; Faccinelli, Martin; Jelinek, Moriz; Schustereder, Werner; Laven, Johannes G.; Schulze, Hans‐Joachim; Hadley, Peter; Pizzini, Sergio; Kissinger, Gudrun
Abstract Electron Beam Induced Current (EBIC) measurements were used to produce cross sectional images of superjunction power transistors. These images show how the depletion width expands under reverse bias. Superjunctions are alternating p‐ and n‐type doped vertical columns placed between drain and source in a power transistor (Deboy et al., in: Proc. IEDM, 983–685 (1998); Lorenz et al., in: Proc. PCIM Europe, 250–258 (1998)). These columns allow a higher substrate doping of the drift region, resulting in a lower on‐state resistance while still maintaining a high breakdown voltage. When the device is reverse biased, the space charge region of the superjunction should expand symmetrically due to the homogeneous doping (in the n and p region) until the complete device depletes. The depletion process was also visualized using voltage contrast (VC) measurements. Here the secondary electron signal was detected when the device was reverse biased. We show that EBIC and VC measurements can provide valuable input for process tuning and process simulations, enabling the use of smaller dimensions and higher doping levels